Are mutual fund investors loss averse? Evidence from China. Issue 2 (22nd September 2020) - Jiang, Jie; Shrider, David G.; Ting, Huangwen; Wu, Yanran
Abstract: Research shows that many investors are loss averse (reluctant to sell investments that have lost value). However, there is open debate about whether mutual fund investors suffer from loss aversion. We use over 300, 000 Chinese mutual fund investor accounts from five open‐end funds to test for loss aversion using survival analysis controlling for time‐varying covariates (Cox analysis). We find strong evidence of loss aversion as these investors are between 60% and 91% less likely to sell a fund that is down in value across the five funds. We also find that more sophisticated investors are less loss averse.